2009
DOI: 10.1016/s1875-9572(09)60043-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations, Laboratory Findings and Complications of Pediatric Scrub Typhus in Eastern Taiwan

Abstract: Scrub typhus should be considered in children with fever and hepatic dysfunction, particularly in those with a history of environmental exposure in an endemic area for scrub typhus. The presence of an eschar offers an important diagnostic clue, but not for all cases. Children with scrub typhus may develop serious complications and may even die if appropriate treatment is not given. Doxycycline is an effective antibiotic for pediatric scrub typhus in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 13 publications
9
28
0
Order By: Relevance
“…The incidence of hepatosplenomegaly, lymphadenopathy, thrombocytopenia and hypoalbuminemia noted in our study was similar to other studies 4,6,9,10,11,12 . Kim et al observed signifi cant J. Nepal Paediatr.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of hepatosplenomegaly, lymphadenopathy, thrombocytopenia and hypoalbuminemia noted in our study was similar to other studies 4,6,9,10,11,12 . Kim et al observed signifi cant J. Nepal Paediatr.…”
Section: Discussionsupporting
confidence: 92%
“…Cent percent of the patients presented with undifferentiated fever which is consistent with the result of the study conducted [20,21] and they had found fever in 100% of the patients. Similarly, Ogawa [22] had found fever in 98% of the patients.…”
Section: Discussionsupporting
confidence: 89%
“…This may be related to prevailing favorable conditions in rural areas related to source, vector and transmission dynamics of the scrub typhus. [4][5][6]10,[18][19][20][21][22][27][28][29][30][31][32] Other important finding similar to other studies was the increase in cases during cooler months from September to January. Rainy seasons favors growth of grassy vegetation which helps in increase in vector population and interaction with human host.…”
Section: Discussionsupporting
confidence: 64%
“…Other studies reported varied occurrence of hepatomegaly (26%-98%) and splenomegaly (17%-88%). 1,3,[9][10][11][12][18][19][20][21][22][28][29][30][31][32] Presence of Eschar, a classical sign of the vector bite which varied between 11% and 69% in previous studies, was noted in 38.6% of the cases in the present study. Overall the findings on signs and symptoms in this study population were similar to other studies among children.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation